Accountability in a developmental government - Tran, Quyet Thang (2020)
A developmental state in which the developmental Government plays a key role is becoming a valuable reference for many nations in the world that wish to promote rapid and sustainable social and economic development through an appropriate pattern of operation. However, the application of new concepts and ideas always comes with challenges, and for a developmental Government, autocracy and authoritarianism can potentially occur, which corrupts power and limits freedom and democracy. Therefore, it is essential to have many mechanisms to operate a developmental Government, including accountability.